At Westonci.ca, we provide clear, reliable answers to all your questions. Join our vibrant community and get the solutions you need. Discover precise answers to your questions from a wide range of experts on our user-friendly Q&A platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
To find the equation of a line that is perpendicular to the given line \( y + 1 = -3(x - 5) \) and passes through the point \((4, -6)\), let's follow these steps:
1. Determine the slope of the original line:
- The given equation \( y + 1 = -3(x - 5) \) can be rewritten in slope-intercept form \( y = mx + b \).
- Starting with \( y + 1 = -3(x - 5) \), distribute the \(-3\):
[tex]\[ y + 1 = -3x + 15 \][/tex]
- Isolate \( y \) to get:
[tex]\[ y = -3x + 14 \][/tex]
- From this, we see that the slope \( m \) of the original line is \(-3\).
2. Find the slope of the perpendicular line:
- The slope of a line perpendicular to another is the negative reciprocal of the original line's slope.
- The negative reciprocal of \(-3\) is \(\frac{1}{3}\). Hence, the slope \( m \) of the perpendicular line is \(\frac{1}{3}\).
3. Use the point-slope formula to find the equation:
- The point-slope form of a line's equation is \( y - y_1 = m(x - x_1) \), where \( m \) is the slope and \((x_1, y_1) \) is a point on the line.
- Here, \( (x_1, y_1) = (4, -6) \) and \( m = \frac{1}{3} \).
- Substitute these values into the point-slope form:
[tex]\[ y - (-6) = \frac{1}{3}(x - 4) \][/tex]
- Simplify this equation:
[tex]\[ y + 6 = \frac{1}{3}(x - 4) \][/tex]
4. Select the correct answer choice:
- Comparing this final form with the given options, we see that it matches option D:
[tex]\[ y + 6 = \frac{1}{3}(x - 4) \][/tex]
Therefore, the equation of the line that is perpendicular to \( y + 1 = -3(x - 5) \) and passes through the point \((4, -6)\) is:
[tex]\[ \boxed{y + 6 = \frac{1}{3}(x - 4)} \][/tex]
1. Determine the slope of the original line:
- The given equation \( y + 1 = -3(x - 5) \) can be rewritten in slope-intercept form \( y = mx + b \).
- Starting with \( y + 1 = -3(x - 5) \), distribute the \(-3\):
[tex]\[ y + 1 = -3x + 15 \][/tex]
- Isolate \( y \) to get:
[tex]\[ y = -3x + 14 \][/tex]
- From this, we see that the slope \( m \) of the original line is \(-3\).
2. Find the slope of the perpendicular line:
- The slope of a line perpendicular to another is the negative reciprocal of the original line's slope.
- The negative reciprocal of \(-3\) is \(\frac{1}{3}\). Hence, the slope \( m \) of the perpendicular line is \(\frac{1}{3}\).
3. Use the point-slope formula to find the equation:
- The point-slope form of a line's equation is \( y - y_1 = m(x - x_1) \), where \( m \) is the slope and \((x_1, y_1) \) is a point on the line.
- Here, \( (x_1, y_1) = (4, -6) \) and \( m = \frac{1}{3} \).
- Substitute these values into the point-slope form:
[tex]\[ y - (-6) = \frac{1}{3}(x - 4) \][/tex]
- Simplify this equation:
[tex]\[ y + 6 = \frac{1}{3}(x - 4) \][/tex]
4. Select the correct answer choice:
- Comparing this final form with the given options, we see that it matches option D:
[tex]\[ y + 6 = \frac{1}{3}(x - 4) \][/tex]
Therefore, the equation of the line that is perpendicular to \( y + 1 = -3(x - 5) \) and passes through the point \((4, -6)\) is:
[tex]\[ \boxed{y + 6 = \frac{1}{3}(x - 4)} \][/tex]
Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.